2016
DOI: 10.6007/ijarbss/v5-i12/1961
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Product Development Strategy on Performance in Sugar Industry in Kenya

Abstract: The purpose of this research was to examine empirically the effects of new product development strategy on company performance. To do so, two indicators of product development strategy which include development of new product and improvement of existing products were considered as independent variable indicators while performance measures were total output turnover, profitability, sales quantities and capacity utilization. The sugar industry in Kenya was chosen as the empirical context for the present study's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
3
11
0
Order By: Relevance
“…The participants agreed strongly that design capabilities positively influence organizational performance and Propensity to purchase a product and perceived quality are influenced by product form as displayed by the 4.60 and 4.51 means respectively and respective SD of 0.40 and 0.49. This concurs with Mbithi, Muturi and Rambo (2015) who looked at how the Kenyan sugar industry's performance is affected by product design capability and the findings indicated that other than sugar, introducing any other new product was hugely minimal while branding and packaging was adopted to improve the current products.…”
Section: Product Design Capabilitysupporting
confidence: 79%
“…The participants agreed strongly that design capabilities positively influence organizational performance and Propensity to purchase a product and perceived quality are influenced by product form as displayed by the 4.60 and 4.51 means respectively and respective SD of 0.40 and 0.49. This concurs with Mbithi, Muturi and Rambo (2015) who looked at how the Kenyan sugar industry's performance is affected by product design capability and the findings indicated that other than sugar, introducing any other new product was hugely minimal while branding and packaging was adopted to improve the current products.…”
Section: Product Design Capabilitysupporting
confidence: 79%
“…The market development strategy has a significant predictive effect on performance through sales volume, primarily when the company pursues market access in new geographic areas. Thus, expanding into new market segments that involve capturing consumers who previously did not use the product can affect company capacity and sales volume (Mbithi et al , 2015). Jose Mas-Ruiz et al (2002) recommend a concentration strategy in external expansion by emphasizing that large market shares in several vital markets generate long-term benefits.…”
Section: Discussionmentioning
confidence: 99%
“…According to Mbithi et al, (2016), new services or programs or product are helpful to the financial health of universities. Universities must keep on coming up with new products since with time the programs are adopted by other universities therefore profitability cannot be sustained for a longer period of time (Ayuya, 2015).…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Universities must keep on coming up with new products since with time the programs are adopted by other universities therefore profitability cannot be sustained for a longer period of time (Ayuya, 2015). A number of studies relates innovation and product development and their positive effects of profitability and overall organizational performance (Bonner et al, 2002;Cohen et al, 1996;B. Mbithi et al, 2016;Zhang et al, 2009).…”
Section: Empirical Reviewmentioning
confidence: 99%